(untitled) (مجلة المنصور, 2022)
The importance of this study lies in shedding the light on the impact of Islam and Prophet Mohammed (peace be upon him) on the western culture and English literature in particular. While some writers were looking at Islam as a dangerous element, others were completely taken by the oriental spirit of Arabic and Islamic culture and glorifying it. Writers from Chaucer to later ones mostly make references to this impact showing how vast was the gap of misunderstanding between the east and the West. Thus, this study aims at breaking the barrier between East and West in its three sections as it introduces the meaning of Islam and its common features with other religions in the first section. The second section briefly presents writers’ reflection on Islam in English literature in some prominent historical phases. The third section dominantly focuses on the equivalent Qur’anic and Biblical images in John Bunyan’s fiction The Pilgrim’s Progress.